Prevalence rates of prolonged grief disorder are overestimated - Maarten C. Eisma (European Journal of Psychotraumatology)
Prolonged grief disorder (PGD) has been included in the International Classification of Diseases 11th edition (ICD-11) and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR). Accurate assessment of the prevalence of PGD is imperative to healthcare policy and practice. Systematic reviews and meta-analyses of at-risk bereaved subgroups (e.g. those bereaved by natural disasters, unnatural causes, and COVID-19) yield very high prevalence rates (24–87%). These findings appear at odds with the well-established finding that most people respond to major negative life events resiliently. This letter explores two potential explanations for overestimated prevalence rates of PGD. First, non-probability sampling, typical to research in vulnerable bereaved subgroups, leads to overestimation of prevalence rates of PGD relative to probability sampling. Secondly, based on epidemiological research in depression and post-traumatic stress disorder, we consider the risk that the use of self-report scales, typical to grief research, may lead to overestimation of prevalence rates compared to clinical interviewing. We recommend international research, based on probability sampling, that systematically assesses loss characteristics and circumstances as well as ICD-11 and DSM-5-TR PGD symptoms, using validated scales, and, ideally, clinical interviewing in a subset of participants, to enable more accurate assessment of prevalence rates of PGD in different bereaved populations.